International responsability of states for the peaceful use of nuclear energy. The need for international legislative action - Zaldívar, Enrique E. (Comisión Nacional de Energía Atómica (Argentina), 1960)
Fil: Zaldívar, Enrique. Comisión Nacional de Energía Atómica; Argentina